SIWAKOT APPLICATION: REVOLUTIONIZING TOURISM REVENUE IN BEKASI - Pramukty, Rachmat; Yulaeli, Tri; Arumi, Mira (JRAK, 2024)
The research evaluated the effectiveness of the City Tourism Information System (SIWAKOT) in boosting Bekasi City's Regional Original Revenue (PAD) through tourism. It analyzed SIWAKOT's impact on revenue generation and its role in the development of the tourism sector. Methodologically, it employed primary data analysis, stakeholder interviews and surveys focused on Bekasi tourism. The findings indicated that SIWAKOT enhanced tourism information management, expanded promotional reach, and improved tourist experiences, therefore, increasing visitor numbers and economic activities. The research suggested implementing SIWAKOT or similar strategies to leverage Bekasi’s tourism potential for revenue growth. It has contributed to innovative PAD augmentation strategies, emphasizing SIWAKOT's transformative potential and the importance of utilizing tourism resources for sustainable revenue enhancement in Bekasi.